Polymerizable liquid crystal compound, polymerizable liquid crystal composition, retardation film, elliptically polarizing plate, and organic EL display device

A polymerizable liquid crystal compound with enhanced solubility addresses the precipitation issue, enabling the production of high-quality retardation films and elliptically polarizing plates with improved alignment and optical properties.

JP7613950B2Active Publication Date: 2025-01-15SUMITOMO CHEM CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021032570
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-23
Filing Date
2021-03-02
Publication Date
2025-01-15
Estimated Expiration
2041-03-02

AI Technical Summary

Technical Problem

Polymerizable liquid crystal compounds with low solubility in solvents can precipitate during film formation, leading to alignment defects in optical films.

Method used

Development of a polymerizable liquid crystal compound with a specific molecular structure, represented by formulas (I) and (II), which enhances solubility in solvents, preventing precipitation and ensuring uniform film formation.

Benefits of technology

The high solubility of the new liquid crystal compounds allows for the production of optical films with improved alignment and optical properties, reducing defects and enhancing the performance of retardation films and elliptically polarizing plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613950000001
    Figure 0007613950000001
  • Figure 0007613950000002
    Figure 0007613950000002
  • Figure 0007613950000003
    Figure 0007613950000003
Patent Text Reader

Abstract

To provide a polymerizable liquid crystal compound which solely exhibits high solubility in a solvent and can improve the solubility in a solvent of other polymerizable liquid crystal compounds capable of constituting an optical film.SOLUTION: There is provided a polymerizable liquid crystal compound represented by the formula (1). [M represents a divalent alicyclic hydrocarbon group, B1 and B2 represent -Ra3COORa4-, -Ra5OCORa6 or the like, A1 and A2 represent a divalent alicyclic hydrocarbon group or an aromatic group, L1 and L2 represent -O-, -COO- or -OCO-, Ea and Eb represent an alkanediyl group having 1 to 12 carbon atoms, P is an acryloyloxy group or a methacryloyloxy group, when a smaller one of the total number of carbon atoms in a group represented by Ea and the total number of carbon atoms in a group represented by Eb is defined as N1 and a larger one is defined as N2, N1 is 2 to 6, N2 is 6 to 12 and the relation of 1<N2-N1<10 is satisfied.]SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymerizable liquid crystal compound, a polymerizable liquid crystal composition containing the polymerizable liquid crystal compound, a retardation film formed from a cured product of the polymerizable liquid crystal composition, and an elliptical polarizing plate and an organic EL display device each including the retardation film. [Background technology]

[0002] As an optical film such as a retardation film used in a flat panel display device (FPD), for example, there is an optical film obtained by dissolving a polymerizable liquid crystal compound in a solvent, applying the resulting coating liquid to a supporting substrate, and then polymerizing the coating liquid. As a polymerizable liquid crystal compound for forming such an optical film, for example, a nematic liquid crystal compound having a rod-shaped structure in which a plurality of six-membered rings are linked is known (for example, Patent Document 1).

[0003] On the other hand, a retardation film is required to have one of its characteristics to be capable of uniform polarization conversion in the entire wavelength range, and it is known that, in theory, uniform polarization conversion is possible in a wavelength range where the value [Re(λ) / Re(550)] obtained by dividing the retardation value Re(λ) at a certain wavelength λ by the retardation value Re(550) at 550 nm is close to 1, or in a wavelength range showing the inverse wavelength dispersion of [Re(450) / Re(550)]<1. A polymerizable liquid crystal compound capable of forming such a retardation film is disclosed in, for example, Patent Document 2. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-24438 A [Patent Document 2] JP 2011-207765 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the coating solution used for producing an optical film, the polymerizable liquid crystal compound may have poor solubility in a solvent depending on its molecular structure. Such a polymerizable liquid crystal compound having low solubility may precipitate or crystallize and precipitate in the coating solution, and such precipitation or precipitation of the polymerizable liquid crystal compound may not only reduce film-forming properties but also cause alignment defects in the obtained optical film.

[0006] Therefore, an object of the present invention is to provide a polymerizable liquid crystal compound that can exhibit high solubility in a solvent by itself. [Means for solving the problem]

[0007] The present invention provides the following preferred embodiments. [1] Formula (I): [ka] [In formula (I), M represents a divalent alicyclic hydrocarbon group, a hydrogen atom contained in the divalent alicyclic hydrocarbon group is optionally substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent alicyclic hydrocarbon group is optionally substituted with an oxygen atom, a sulfur atom, or a nitrogen atom; B 1 and B. 2 each independently represents an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 O.C.O.R. a6 -, -R a7 OC=OOR a8 -, -OR b O-, -C(=O)-NR c -, -N=N-, -CR c =CR d - or -C≡C-, where R a1 ~R a8is each independently a single bond or an alkylene group having 1 to 4 carbon atoms, and R b is an alkylene group having 1 to 4 carbon atoms, and R c and R d each represent an alkyl group having 1 to 4 carbon atoms or a hydrogen atom, A 1 and A 2 each independently represent a divalent alicyclic hydrocarbon group or an aromatic group, and the hydrogen atoms contained in the divalent alicyclic hydrocarbon group or aromatic group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent alicyclic hydrocarbon group or aromatic group may be substituted with an oxygen atom, a sulfur atom or a nitrogen atom, L 1 and L 2 each independently represent -O-, -COO- or -OCO-, E a and E b each independently represent an alkanediyl group having 1 to 12 carbon atoms, where the hydrogen atoms contained in the alkanediyl group may be substituted with an alkyl group having 1 to 4 carbon atoms or a halogen atom, and the -CH2- not adjacent to L 1 or L 2 may be substituted with -O- or -S- (provided that when there are a plurality of -O- and / or -S- in E a and E b , they are not adjacent to each other) P is an acryloyloxy group or a methacryloyloxy group, E a When the total number of carbon atoms in the group represented by is N1 and the total number of carbon atoms in the group represented by E b is N2, where N1 is 2 to 6 and N2 is 6 to 12, satisfying the relationship 1 < N2 - N1 < 10] A polymerizable liquid crystal compound represented by. [2] The polymerizable liquid crystal compound according to [1], wherein M is a divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms. [3]A 1 and A 2 each independently represents a divalent aromatic group, a hydrogen atom contained in the divalent aromatic group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. [4]B 1 and B. 2 are each independently -COO- or -OCO-. [5] A polymerizable liquid crystal compound according to any one of [1] to [4] above, and a liquid crystal compound of formula (II): [ka] [In formula (II), Ar is a divalent group having at least one aromatic ring, and the aromatic ring constituting the divalent group may contain at least one of a nitrogen atom, an oxygen atom, and a sulfur atom, and the total number N of π electrons contained in the aromatic rings constituting Ar is π is greater than or equal to 12 and less than 36, G 1 and G 2 each independently represents a divalent alicyclic hydrocarbon group, a hydrogen atom contained in the alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and -CH- contained in the alicyclic hydrocarbon group may be substituted by -O-, -S-, or -NH-; B 3 and B. 4 each independently represents a single bond or a divalent linking group, A 3 and A 4each independently represents a divalent alicyclic hydrocarbon group having 3 to 20 carbon atoms or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a hydrogen atom contained in the alicyclic hydrocarbon group and the aromatic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms which may be substituted with a fluorine atom, an alkoxy group having 1 to 4 carbon atoms which may be substituted with a fluorine atom, a cyano group or a nitro group, and -CH2- contained in the alicyclic hydrocarbon group is -O-, -S- or -NR 1 -, -CH(-)- contained in the alicyclic hydrocarbon group may be replaced by -N(-)-, R 1 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, L 3 ~L 6 each independently represents -O-, -COO- or -OCO-; E c and E d each independently represents an alkanediyl group having 1 to 17 carbon atoms, a hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and -CH- contained in the alkanediyl group may be replaced with -O- or -CO-, P 1 and P 2 each independently represents a polymerizable group. and a polymerizable liquid crystal compound represented by the formula: [6] The polymerizable liquid crystal composition according to [5] above, wherein the polymerizable liquid crystal compound represented by formula (II) exhibits a maximum absorption in the wavelength range of 300 nm or more and 400 nm or less. [7] The polymerizable liquid crystal composition according to [5] or [6] above, comprising the polymerizable liquid crystal compound represented by formula (II) in an amount of 0.1 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the polymerizable liquid crystal compound represented by formula (I). [8] A retardation film comprising a cured product of the polymerizable liquid crystal composition according to any one of the above [5] to [7], the cured product being a liquid crystal cured film obtained by curing the polymerizable liquid crystal composition in an aligned state. [9] The liquid crystal cured film is represented by the formulas (1), (2) and (3): Re(450) / Re(550)≦1.00 (1) 1.00≦Re(650) / Re(550) (2) 100nm≦Re(550)≦180nm (3) [In the formula, Re(λ) represents an in-plane retardation value of the cured liquid crystal film at a wavelength of λ nm, and Re=(nx(λ)-ny(λ))×d (d represents the thickness of the cured liquid crystal film, nx represents the principal refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film in an index ellipsoid formed by the cured liquid crystal film, and ny represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film and perpendicular to the direction of nx in an index ellipsoid formed by the cured liquid crystal film).] The retardation film according to [8] above, having optical properties represented by the following formula:

[10] The liquid crystal cured film is represented by the formulas (4), (5) and (6): Rth(450) / Rth(550)≦1.00 (4) 1.00≦Rth(650) / Rth(550) (5) -100nm≦Rth(550)≦-40nm (6) [wherein Rth(λ) represents a retardation value in the thickness direction of the cured liquid crystal film at a wavelength of λ nm, and Rth=((nx(λ)+ny(λ)) / 2-nz)×d (wherein d represents the thickness of the cured liquid crystal film, nx represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film in the index ellipsoid formed by the cured liquid crystal film, ny represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film and perpendicular to the direction of nx in the index ellipsoid formed by the cured liquid crystal film, and nz represents the refractive index at a wavelength of λ nm in a direction perpendicular to the plane of the cured liquid crystal film in the index ellipsoid formed by the cured liquid crystal film). The retardation film according to [8] above, having optical properties represented by the following formula:

[11] An elliptically polarizing plate comprising the retardation film according to any one of [8] to

[10] above and a polarizing film.

[12] An organic electroluminescence display device comprising the elliptically polarizing plate according to

[11] above.

[13] A flexible image display device comprising the elliptically polarizing plate according to

[11] above.

[14] The flexible image display device according to

[13] , further comprising a window and a touch panel touch sensor. Effect of the Invention

[0008] According to the present invention, it is possible to provide a polymerizable liquid crystal compound that can exhibit high solubility in a solvent by itself. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.

[0010] <Polymerizable liquid crystal compound> The polymerizable liquid crystal compound of the present invention has the formula (I): [ka] Hereinafter, the polymerizable liquid crystal compound represented by formula (I) will also be referred to as "polymerizable liquid crystal compound (I)".

[0011] In formula (I), M represents a divalent alicyclic hydrocarbon group. A hydrogen atom contained in the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom.

[0012] Examples of the divalent alicyclic hydrocarbon group for M in formula (I) include divalent alicyclic hydrocarbon groups having 3 to 18 carbon atoms. The divalent alicyclic hydrocarbon group preferably has 4 to 15 carbon atoms, more preferably 5 to 10 carbon atoms, further preferably 5 to 8 carbon atoms, and particularly preferably 5 or 6 carbon atoms.

[0013] The hydrogen atoms contained in the divalent alicyclic hydrocarbon group may each be independently substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group.

[0014] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom, with a fluorine atom, a chlorine atom or a bromine atom being preferred.

[0015] Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, and a tert-butyl group. An alkyl group having 1 to 3 carbon atoms is preferable, an alkyl group having 1 or 2 carbon atoms is more preferable, and a methyl group is even more preferable. Examples of the fluoroalkyl group having 1 to 4 carbon atoms include those in which a hydrogen atom contained in the alkyl group having 1 to 4 carbon atoms has been substituted with a fluorine atom.

[0016] Examples of the alkoxy group having 1 to 4 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a sec-butoxy group, and a tert-butoxy group. An alkoxy group having 1 to 3 carbon atoms is preferable, an alkoxy group having 1 or 2 carbon atoms is more preferable, and a methoxy group is even more preferable.

[0017] The carbon atoms contained in the divalent alicyclic hydrocarbon group may each be independently substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. One carbon atom may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom, or two or more carbon atoms may each be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. For example, -CH2- (methylene group) contained in the divalent alicyclic hydrocarbon group may each be independently substituted with -O-, -S-, -NH-, or -NR 1 Each of the -CH(-)- contained in the alicyclic hydrocarbon group may be independently replaced by -N(-)-. 1represents an alkyl group having 1 to 4 carbon atoms, and hydrogen atoms contained in the alkyl group may each independently be substituted with a fluorine atom.

[0018] Examples of the divalent alicyclic hydrocarbon group include groups represented by the following formulae (m-1) to (m-4). The -CH2- contained in the alicyclic hydrocarbon group is -O-, -S-, -NH- or -NR 1 Examples of the divalent alicyclic hydrocarbon group substituted with - include groups represented by the following formulae (m-5) to (m-8). Examples of the divalent alicyclic hydrocarbon group in which -CH(-)- contained in the alicyclic hydrocarbon group is replaced with -N(-)- include groups represented by the following formulae (m-9) and (m-10). These are preferably 5- or 6-membered alicyclic hydrocarbon groups.

[0019] [ka]

[0020] From the viewpoint of wavelength dispersion, the divalent alicyclic hydrocarbon group is preferably a cycloalkanediyl group represented by formula (M-1), more preferably a cyclohexane-1,4-diyl group, and even more preferably a trans-cyclohexane-1,4-diyl group.

[0021] B in formula (I) 1 and B. 2 each independently represents an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 O.C.O.R. a6 -, -R a7 OC=OOR a8 -, -OR b O-, -C(=O)-NR c -, -N=N-, -CR c =CR d - or -C≡C-. R a1 ~R a8are each independently a single bond or an alkylene group having 1 to 4 carbon atoms; R b is an alkylene group having 1 to 4 carbon atoms, R c and R d is an alkyl group having 1 to 4 carbon atoms or a hydrogen atom.

[0022] B 1 and B. 2 are each independently preferably -OR a2-1 -, -CH2-, -CH2CH2-, -COOR a4-1 -OR- a6-1 -, where R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and B. 2 are each independently more preferably -O-, -CH2CH2-, -COO-, -COOCH2CH2- or -OCO-, further preferably -O-, -COO- or -OCO-, particularly preferably -COO- or -OCO-. 1 and B. 2 may be the same or different. 1 and B 2 are identical to each other, B when viewed from the center 1 and B 2 This means that the structures of A and B are identical to each other. 1 and A 2 , L 1 and L 2 , E a and E b The same is true for the relationship in

[0023] A in formula (I) 1 and A 2each independently represents a divalent alicyclic hydrocarbon group or aromatic group. A hydrogen atom contained in the divalent alicyclic hydrocarbon group or aromatic group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group. In addition, a carbon atom constituting the divalent alicyclic hydrocarbon group or aromatic group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom.

[0024] A in formula (I) 1 and A 2 Examples of the divalent alicyclic hydrocarbon group in include the groups exemplified as the divalent alicyclic hydrocarbon group in M. Examples of the divalent aromatic group include divalent aromatic hydrocarbon groups having about 6 to 20 carbon atoms and represented by the following formulas (a-1) to (a-8). [ka]

[0025] Some of the hydrogen atoms in the groups represented by the above formulas (a-1) to (a-8) may be substituted with an alkyl group having about 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an i-propyl group, or a t-butyl group; an alkoxy group having about 1 to 4 carbon atoms, such as a methoxy group or an ethoxy group; a trifluoromethyl group; a trifluoromethyloxy group; a cyano group; a nitro group; or a halogen atom, such as a fluorine atom, a chlorine atom, or a bromine atom.

[0026] A in formula (I) 1 and A 2 are each independently preferably a divalent aromatic group, and a hydrogen atom contained in the divalent aromatic group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. 1 and A 2are each independently preferably a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, further preferably a 1,4-phenylenediyl group which may be substituted with a methyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group. 1 and A 2 may be the same or different. A 1 and A 2 At least one of A is preferably a divalent aromatic group, and from the viewpoint of exhibiting good liquid crystal properties, 1 and A 2 It is more preferable that each of the above groups is a 1,4-phenylenediyl group.

[0027] L in formula (I) 1 and L 2 each independently represents -O-, -COO- or -OCO-.

[0028] E in formula (I) a and E b each independently represents an alkanediyl group having 1 to 12 carbon atoms. A hydrogen atom contained in the alkanediyl group may be substituted with an alkyl group having 1 to 4 carbon atoms or a halogen atom. 1 or L 2 -CH2- not adjacent to E may be replaced by -O- or -S-. a and E b When a plurality of -O- and / or -S- are present in the ring, they are not adjacent to each other.

[0029] E a and E b The number of carbon atoms in the alkanediyl group represented by the following formula is independently preferably 2 or more, more preferably 3 or more, and is preferably 11 or less, more preferably 8 or less.

[0030] In formula (I), E aThe total number of carbon atoms in the group represented by and E b When the smaller value of the total number of carbon atoms in the group represented by is N1 and the larger value is N2, N1 is 2 to 6 and N2 is 6 to 12. Also, N1 and N2 satisfy the relationship 1 < N2 - N1 < 10. E in formula (I) a The group represented by and E b When the group represented by has the specific number of carbon atoms and the group represented by also has the specific number of carbon atoms, and the number of carbon atoms of both is in the relationship of more than 1 and less than 10, the solubility in various solvents (for example, cyclopentanone, o-xylene, 2-methylpyrrolidone, chloroform) is likely to be improved. The reason is not clear, but it is considered that since the compound has an asymmetric structure, it is difficult to precipitate, and as a result, the solubility is improved. The value of N2 - N1 is preferably 2 or more, more preferably 3 or more, and preferably 9 or less, more preferably 8 or less, and even more preferably 7 or less. In this specification, the total number of carbon atoms in the group represented by the above E a and the total number of carbon atoms in the group represented by E b each mean the total number of carbon atoms constituting the main chain of the compound represented by formula (I), and do not include the number of carbon atoms contained as substituents on the carbon atoms constituting the main chain.

[0031] In formula (I), P is an acryloyloxy group or a methacryloyloxy group.

[0032] In formula (I), E a and E b have different structures from each other. Therefore, the polymerizable liquid crystal compound (I) has a divalent alicyclic hydrocarbon group represented by M as the center, and P - E a -L 1 -A 1 -B 1 - represented structure and -B 2 -A 2 -L 2 -E bThe polymerizable liquid crystal compound (I) has an asymmetric molecular structure with respect to the divalent alicyclic hydrocarbon group represented by M, and the ring structures in the symmetrical relationship with the structure represented by M are the same. 1 and A 2 and are preferably the same, and PE in formula (I) a -L 1 -A 1 -B 1 - and -B 2 -A 2 -L 2 -E b The structure represented by -P and the asymmetric molecular structure represented by E a and E b It is asymmetric only in the structure of B 1 and B 2 , A 1 and A 2 and L 1 and L 2 and preferably have the same structure as each other.

[0033] Examples of the polymerizable liquid crystal compound (I) include compounds represented by the following formulas (Ia) to (Ig). [ka]

[0034] The method for producing the polymerizable liquid crystal compound (I) of the present invention is not particularly limited, and the compound can be produced by appropriately combining known organic synthesis reactions (e.g., condensation reaction, esterification reaction, Williamson reaction, Ullmann reaction, Wittig reaction, Schiff base formation reaction, benzylation reaction, Sonogashira reaction, Suzuki-Miyaura reaction, Negishi reaction, Kumada reaction, Hiyama reaction, Buchwald-Hartwig reaction, Friedel-Crafts reaction, Heck reaction, aldol reaction, etc.) described in Methoden der Organischen Chemie, Organic Reactions, Organic Syntheses, Comprehensive Organic Synthesis, New Experimental Chemistry Lectures, etc., depending on the structure of the compound.

[0035] For example, B in formula (I) 1 and B. 2 A polymerizable liquid crystal compound represented by the following formula (I'), in which *-COO- (* means a bonding site with M), can be obtained by an esterification reaction between a carboxylic acid compound represented by the following formula (I-1) and an alcohol compound represented by formula (I-2). [ka] [In formula (I'), M, A 1 , A 2 , L 1 , L 2 , E a , E b and P are M, A in formula (I), respectively. 1 , A 2 , L 1 , L 2 , E a , E b and P have the same meaning. [ka] [In formula (I-1), M, B 1 , A 1 , L 1 , E a and P are M, B in formula (I). 1 , A 1 , L 1 , E a and P have the same meaning. [ka] [In formula (I-2), A 2 , L 2 , E b and P is A in formula (I). 2 , L 2 , E b and P have the same meaning.

[0036] M and B in formula (I-1) 1 , A 1 , L 1 , E a and P, and A in formula (I-2)2 , L 2 , E b and P are determined depending on the corresponding molecular structure of the desired polymerizable liquid crystal compound (I).

[0037] The compound represented by formula (I-1) and the compound represented by formula (I-2) are each represented by M, B 1 , A 1 , L 1 , E a and P or A 2 , L 2 , E b and P can be produced by synthesizing and bonding each of the structural units by appropriately combining known organic synthesis reactions according to the structure. Specifically, for example, it can be prepared from a compound having a structure corresponding to the structure of the desired polymerizable liquid crystal compound (I) according to the method described in JP-A-2010-24438 or the like.

[0038] For example, B in formula (I-1) 1 is -COO-, the compound represented by formula (I-1) is represented by the following formula (I-1a): [ka] (In formula (I-1a), M has the same meaning as M in formula (I).) and a dicarboxylic acid compound (I-1a) represented by the following formula (I-1b): [ka] [In formula (I-1b), A 1 , L 1 , E a and P is A in formula (I). 1 , L 1 , E a and P have the same meaning. The compound (I-1b) can be obtained by an esterification reaction with an alcohol compound (I-1b) represented by the following formula:

[0039] The compound represented by formula (I-2) may be a compound in which two carboxyl groups are bonded to a divalent alicyclic hydrocarbon group corresponding to the alicyclic hydrocarbon group M in formula (I) in the desired polymerizable liquid crystal compound (I).

[0040] The esterification reaction between the carboxylic acid compound (I-1) and the alcohol compound (I-2) is preferably carried out in the presence of a condensing agent. By carrying out the esterification reaction in the presence of a condensing agent, the esterification reaction can be carried out efficiently and quickly.

[0041] Examples of the condensation agent include 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide metho-para-toluenesulfonate, dicyclohexylcarbodiimide, diisopropylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (commercially available as water-soluble carbodiimide: WSC), bis(2,6-diisopropylphenyl)carbodiimide, Imides and carbodiimide compounds such as bis(trimethylsilyl)carbodiimide, 2-methyl-6-nitrobenzoic anhydride, 2,2'-carbonylbis-1H-imidazole, 1,1'-oxalyldiimidazole, diphenylphosphoryl azide, 1(4-nitrobenzenesulfonyl)-1H-1,2,4-triazole, 1H-benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate, 1H-benzyloxytripyrrolidinophosphonium hexafluorophosphate, N-(1,2,2,2-tetrachloroethoxycarbonyloxy)succinimide, N-carbobenzoxysuccinimide, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, fluoroborate, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, 2-bromo-1-ethylpyridinium tetrafluoroborate, 2-chloro-1,3-dimethylimidazolinium chloride, 2-chloro-1,3-dimethylimidazolinium hexafluorophosphate, 2-chloro-1-methylpyridinium iodide, 2-chloro-1-methylpyridinium para-toluenesulfonate, 2-fluoro-1-methylpyridinium para-toluenesulfonate, and trichloroacetic acid pentachlorophenyl ester.

[0042] The polymerizable liquid crystal compound (I) of the present invention is represented by the following formula (II): [ka] (hereinafter, also referred to as "polymerizable liquid crystal compound (II)"), the compound has good solubility in a solvent.

[0043] In formula (II), Ar is a divalent group having at least one aromatic ring, and the aromatic ring constituting the divalent group may contain at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. The divalent group having an aromatic ring may be a divalent aromatic hydrocarbon group or a divalent aromatic heterocyclic group which may have a substituent. In the present invention, the divalent aromatic hydrocarbon group which may have a substituent means a divalent group containing at least one aromatic hydrocarbon ring, and the divalent aromatic heterocyclic group which may have a substituent means a divalent group containing at least one aromatic heterocyclic ring. The aromatic hydrocarbon ring and aromatic heterocyclic ring referred to here are those in which the number of π electrons in the ring structure is [4n+2] (n represents an integer) according to the Huckel rule (in the case of an aromatic heterocyclic ring, the Huckel rule is satisfied, including the non-covalent bond electron pair on the heteroatom such as -N= or -S-). Ar may contain one aromatic hydrocarbon ring or aromatic heterocyclic ring, or may contain two or more. When it contains one aromatic hydrocarbon ring or aromatic heterocycle, Ar may be a divalent aromatic hydrocarbon group which may have a substituent, or a divalent aromatic heterocyclic group which may have a substituent. When it contains two or more aromatic hydrocarbon rings or aromatic heterocycles, it may contain only aromatic hydrocarbon rings, or only aromatic heterocycles, or it may contain one or more aromatic hydrocarbon rings and one or more aromatic heterocycles. Two or more aromatic hydrocarbon rings and / or aromatic heterocycles may be bonded to each other by a divalent bonding group such as a single bond, -CO-O-, or -O-.

[0044] Examples of aromatic hydrocarbon rings contained in Ar include benzene ring, naphthalene ring, anthracene ring, etc., and benzene ring and naphthalene ring are preferred. Examples of aromatic heterocycles include furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole ring, oxazole ring, benzoxazole ring, and phenanthroline ring. Among them, it is preferred to have a thiazole ring, benzothiazole ring, or benzofuran ring, and it is more preferred to have a benzothiazole group. In addition, when Ar contains a nitrogen atom, it is preferred that the nitrogen atom has π electrons.

[0045] In formula (II), the total number of π electrons contained in Ar is N π is preferably 12 or more, more preferably 14 or more, and even more preferably 16 or more. Also, it is preferably less than 40, more preferably 36 or less, even more preferably 34 or less, and particularly preferably 32 or less.

[0046] Examples of the aromatic group represented by Ar include the following groups.

[0047] [ka]

[0048] In formulae (Ar-1) to (Ar-23), * represents a linking portion, Z 0 , Z 1 and Z 2each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms. 0 , Z 1 and Z 2 may contain a polymerizable group.

[0049] Q 1 and Q 2 are each independently -CR 2’ R 3’ -, -S-, -NH-, -NR 2’ -, -CO- or -O-; R 2’ and R 3’ each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0050] J 1 and J. 2 each independently represents a carbon atom or a nitrogen atom.

[0051] Y 1 , Y 2 and Y 3 each independently represents an optionally substituted aromatic hydrocarbon group or an optionally substituted aromatic heterocyclic group.

[0052] W 1 and W 2 each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom; and m represents an integer of 0 to 6.

[0053] Y 1 , Y 2 and Y 3Examples of the aromatic hydrocarbon group in the formula (I) include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group, of which a phenyl group and a naphthyl group are preferred, and a phenyl group is more preferred. Examples of the aromatic heterocyclic group in the formula (I) include aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one heteroatom, such as a nitrogen atom, an oxygen atom, or a sulfur atom, such as a furyl group, a pyrrolyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group, of which a furyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group are preferred.

[0054] Y 1 , Y 2 and Y 3 may each independently be an optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.

[0055] Z 0 , Z 1 and Z 2 are each preferably independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms; Z 0 is more preferably a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group; Z 1 and Z 2 is more preferably a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group. 0 , Z 1 and Z 2 may contain a polymerizable group.

[0056] Q 1 and Q 2 -NH-, -S-, -NR 2’ -, -O- are preferred, R 2’ is preferably a hydrogen atom, and among these, -S-, -O-, and -NH- are particularly preferable.

[0057] Among the formulae (Ar-1) to (Ar-23), the formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.

[0058] In formulas (Ar-16) to (Ar-23), Y 1 is the nitrogen atom to which it is bonded and Z 0 and may form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include those mentioned above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. This aromatic heterocyclic group may have a substituent. In addition, Y 1 is the nitrogen atom to which it is bonded and Z 0 In addition, it may be the above-mentioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, etc.

[0059] G in formula (II) 1 and G 2 As the polymerizable liquid crystal compound (I), 1 and A 2 The divalent alicyclic hydrocarbon group in the formula (I) is the same as that in the formula (I). 1 and G 2 is preferably a 5- or 6-membered alicyclic hydrocarbon group, more preferably a 6-membered alicyclic hydrocarbon group, still more preferably a cyclohexane-1,4-diyl group, and particularly preferably a trans-cyclohexane-1,4-diyl group. 1 and G 2 may be the same as or different from each other.

[0060] B in formula (II) 3 and B. 4 each independently represents a single bond or a divalent linking group. 3 and B. 4As the divalent linking group in the polymerizable liquid crystal compound (I), 1 and B. 2 The same groups as those exemplified as B in formula (II) are included. 3 and B. 4 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 O.C.O.R. a6 -, -R a7 OC=OOR a8 -, -N=N-, -CR c =CR d - or -C≡C-, where R a1 ~R a8 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms; R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 3 and B. 4 are each independently preferably a single bond, -OR a2-1 -, -CH2-, -CH2CH2-, -COOR a4-1 -OR- a6-1 - and (R a2-1 , R a4-1 , R a6-1 each independently represents a single bond, -CH2-, or -CH2CH2-, more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-, and particularly preferably -COO- or -OCO-. 3 and B. 4 may be the same as or different from each other.

[0061] A in formula (II) 3 and A 4each independently represents a divalent alicyclic hydrocarbon group having 3 to 20 carbon atoms or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms. The hydrogen atoms contained in the alicyclic hydrocarbon group and the aromatic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms which may be substituted with a fluorine atom, an alkoxy group having 1 to 4 carbon atoms which may be substituted with a fluorine atom, a cyano group or a nitro group. In addition, -CH2- contained in the alicyclic hydrocarbon group is -O-, -S- or -NR 1 The -CH(-)- contained in the alicyclic hydrocarbon group may be replaced by -N(-)-. 1 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0062] A in formula (II) 3 and A 4 As the alicyclic hydrocarbon group and the aromatic hydrocarbon group in the polymerizable liquid crystal compound (I), 1 and A 2 In formula (II), A is a group similar to the groups exemplified above. 3 and A 4 are each independently preferably a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-cyclohexanediyl group. 1 and A 2 may be the same or different from each other.

[0063] L in formula (II) 3 ~L 6 Each of L independently represents -O-, -COO- or -OCO-.3 ~L 6 may be the same or different from each other.

[0064] E in formula (II) c and E d Each of E independently represents an alkanediyl group having 1 to 17 carbon atoms. A hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and -CH2- contained in the alkanediyl group may be substituted with -O- or -CO-. c and E d are each independently preferably an optionally substituted alkanediyl group having 4 to 17 carbon atoms, more preferably an optionally substituted alkanediyl group having 4 to 12 carbon atoms. c and E d may be the same or different from each other.

[0065] P in formula (II) 1 and P 2 Each of P independently represents a polymerizable group. 1 or P 2 Examples of the polymerizable group represented by the formula (II) include an epoxy group, a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among these, an acryloyloxy group, a methacryloyloxy group, a vinyl group, and a vinyloxy group are preferred, an acryloyloxy group and a methacryloyloxy group are more preferred, and an acryloyloxy group is even more preferred. In the formula (II), P 1 and P 2 may be the same or different.

[0066] Examples of the polymerizable liquid crystal compound (II) include compounds described in JP-A-2011-207765, JP-A-2008-107767, WO2014 / 010325, and JP-A-2019-003177.

[0067] The polymerizable liquid crystal compound (II) is preferably a polymerizable liquid crystal compound that exhibits a maximum absorption in the wavelength range of 300 nm to 400 nm. When the polymerizable liquid crystal composition contains a photopolymerization initiator, the polymerization reaction and gelation of the polymerizable liquid crystal compound may proceed during long-term storage. However, if the maximum absorption wavelength of the polymerizable liquid crystal compound (II) is within the range of 300 nm to 400 nm, even if the polymerizable liquid crystal compound is exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound due to the reactive species can be effectively suppressed. Therefore, it is advantageous in terms of long-term stability of the polymerizable liquid crystal composition, and the alignment property and the uniformity of the film thickness of the obtained liquid crystal cured film can be improved. The maximum absorption wavelength of the polymerizable liquid crystal compound (II) can be measured using a UV-visible spectrophotometer in a solvent. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound (II), and examples thereof include chloroform and the like.

[0068] The polymerizable liquid crystal composition of the present invention contains a polymerizable liquid crystal compound (I) and a polymerizable liquid crystal compound (II). As the polymerizable liquid crystal compound (I) and the polymerizable liquid crystal compound (II), each of them may contain only one kind, or may contain two or more kinds in combination.

[0069] The polymerizable liquid crystal composition of the present invention has a high solubility in a solvent of the polymerizable liquid crystal compound, and is therefore excellent in the effect of suppressing the occurrence of alignment defects due to the precipitation or deposition of the polymerizable liquid crystal compound during storage or the like. Therefore, by using the polymerizable liquid crystal composition of the present invention, it is possible to form a film without deteriorating the optical properties that the polymerizable liquid crystal compound can originally exhibit, and a liquid crystal cured film having excellent optical properties can be obtained. In addition, compared with the case where the polymerizable liquid crystal compound (I) is dissolved alone in a solvent, it is possible to easily dissolve a larger amount of the polymerizable liquid crystal compound in the same amount or a smaller amount of solvent. Furthermore, it may be possible to dissolve the polymerizable liquid crystal compound in a solvent in which the polymerizable liquid crystal compound (I) or (II) alone is hardly or completely soluble. As a result, the undissolved polymerizable liquid crystal compound is unlikely to remain in the coating liquid, and high coatability during film formation can be ensured, resulting in a polymerizable liquid crystal composition with excellent film formability. Furthermore, it is also advantageous in that the amount of solvent required for preparing the coating liquid can be reduced, and the number of types of solvents that can be selected increases the options for the substrate, alignment film, production conditions, etc. to be used.

[0070] From the viewpoint of easily increasing the compatibility with the polymerizable liquid crystal compound (I) and easily improving the solubility of the polymerizable liquid crystal compound (II) in a solvent, it is preferable that the polymerizable liquid crystal compound (I) and the polymerizable liquid crystal compound (II) have similar structures to each other. 3 and B. 4 are each B in formula (I). 1 and B. 2 and G in formula (II) is the same as 1 and G 2 are each A in formula (I). 1 and A 2 and L in formula (II) is the same as 3 and L 4 are each L in formula (I). 1 and L 2 and P in formula (II) is the same as 1 and P 2 are preferably the same as P in formula (I).

[0071] The polymerizable liquid crystal composition of the present invention contains the polymerizable liquid crystal compound (I) in an amount of preferably 1 part by mass or more and 70 parts by mass or less, more preferably 1 part by mass or more and 50 parts by mass or less, and even more preferably 2 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the polymerizable liquid crystal compound (II). When the content of the polymerizable liquid crystal compound (I) relative to the polymerizable liquid crystal compound (II) is equal to or more than the above lower limit, it is preferable from the viewpoint of wavelength dispersion. Also, when it is equal to or less than the above upper limit, it is easy to sufficiently improve the solubility.

[0072] The polymerizable liquid crystal composition of the present invention may contain a polymerizable liquid crystal compound other than the polymerizable liquid crystal compound (I) and the polymerizable liquid crystal compound (II) as long as the effect of the present invention is not affected. Examples of such a polymerizable liquid crystal compound include a compound represented by the formula (I) represented by E a and E b and generally, a polymerizable liquid crystal compound exhibiting positive wavelength dispersion is exemplified.

[0073] When the polymerizable liquid crystal composition of the present invention contains a polymerizable liquid crystal compound other than the polymerizable liquid crystal compounds (I) and (II), from the viewpoint of obtaining a liquid crystal cured film having excellent optical properties, the total mass of the polymerizable liquid crystal compounds (I) and (II) relative to the total mass of all polymerizable liquid crystal compounds contained in the polymerizable liquid crystal composition is preferably 51 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, and may be 100 mass%.

[0074] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition (total amount of all polymerizable liquid crystal compounds) is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, based on 100 parts by mass of the solid content of the polymerizable liquid crystal composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous in terms of the alignment of the obtained liquid crystal cured film. In this specification, the solid content of the polymerizable liquid crystal composition means all components excluding volatile components such as organic solvents from the polymerizable liquid crystal composition.

[0075] The polymerizable liquid crystal composition of the present invention may further contain, in addition to the polymerizable liquid crystal compounds (I) and (II), additives such as a photopolymerization initiator, an organic solvent, a polymerization inhibitor, a photosensitizer, a leveling agent, etc. Each of these components may be used alone or in combination of two or more.

[0076] The polymerizable liquid crystal composition of the present invention preferably contains a polymerization initiator. The polymerization initiator is a compound that generates reactive species by the contribution of heat or light and can initiate a polymerization reaction of the polymerizable liquid crystal or the like. Examples of the reactive species include active species such as radicals, cations, and anions. Among them, a photopolymerization initiator that generates radicals by light irradiation is preferred from the viewpoint of easy reaction control.

[0077] Examples of photopolymerization initiators include benzoin compounds, benzophenone compounds, benzyl ketal compounds, α-hydroxyketone compounds, α-aminoketone compounds, triazine compounds, iodonium salts, and sulfonium salts.Specific examples include Irgacure (registered trademark) 907, Irgacure 184, Irgacure 651, Irgacure 819, Irgacure 250, Irgacure 369, Irgacure 379, Irgacure 127, Irgacure 2959, Irgacure 754, Irgacure 379EG (all manufactured by BASF Japan Ltd.), Seikuol BZ, Seikuol Z, Seikuol BEE (all manufactured by Seiko Chemical Co., Ltd.), Kayacure (registered trademark) Examples of suitable antibacterial agents include ADEKA CURE BP100 (manufactured by Nippon Kayaku Co., Ltd.), Kayacure UVI-6992 (manufactured by Dow), ADEKA OPTOMER SP-152, ADEKA OPTOMER SP-170, ADEKA OPTOMER N-1717, ADEKA OPTOMER N-1919, ADEKA ARCLES NCI-831, ADEKA ARCLES NCI-930 (all manufactured by ADEKA Corporation), TAZ-A, TAZ-PP (all manufactured by Nippon SiberHegner AG) and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.). In the present invention, the polymerizable liquid crystal composition preferably contains at least one type of photopolymerization initiator, and may contain two or more types of photopolymerization initiators.

[0078] The photopolymerization initiator can fully utilize the energy emitted from the light source and has excellent productivity, so that the maximum absorption wavelength is preferably 300 nm to 400 nm, and more preferably 300 nm to 380 nm, and among them, an α-acetophenone-based polymerization initiator or an oxime-based photopolymerization initiator is preferable.

[0079] Examples of the α-acetophenone polymerization initiator include 2-methyl-2-morpholino-1-(4-methylsulfanylphenyl)propan-1-one, 2-dimethylamino-1-(4-morpholinophenyl)-2-benzylbutan-1-one, and 2-dimethylamino-1-(4-morpholinophenyl)-2-(4-methylphenylmethyl)butan-1-one, and more preferably 2-methyl-2-morpholino-1-(4-methylsulfanylphenyl)propan-1-one and 2-dimethylamino-1-(4-morpholinophenyl)-2-benzylbutan-1-one. Examples of commercially available α-acetophenone compounds include Irgacure 369, 379EG, and 907 (all manufactured by BASF Japan Co., Ltd.) and Seikuol BEE (manufactured by Seiko Chemical Co., Ltd.).

[0080] The oxime-based photopolymerization initiator generates methyl radicals by irradiation with light. The methyl radicals allow the polymerization of the polymerizable liquid crystal compound in the deep part of the liquid crystal cured film to proceed favorably. In addition, from the viewpoint of more efficiently proceeding the polymerization reaction in the deep part of the liquid crystal cured film to be formed, it is preferable to use a photopolymerization initiator that can efficiently use ultraviolet light with a wavelength of 350 nm or more. As photopolymerization initiators that can efficiently use ultraviolet light with a wavelength of 350 nm or more, triazine compounds and oxime ester type carbazole compounds are preferable, and from the viewpoint of sensitivity, oxime ester type carbazole compounds are more preferable. Examples of oxime ester type carbazole compounds include 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), and the like. Commercially available oxime ester carbazole compounds include Irgacure OXE-01, Irgacure OXE-02, Irgacure OXE-03 (all manufactured by BASF Japan Ltd.), ADEKA Optomer N-1919, ADEKA Arcles NCI-831 (all manufactured by ADEKA Corporation), and the like.

[0081] The amount of the photopolymerization initiator added is usually 0.1 parts by mass or more and 30 parts by mass or less, preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and preferably 20 parts by mass or less, more preferably 15 parts by mass or less, based on 100 parts by mass of the polymerizable liquid crystal compound. Within the above range, the reaction of the polymerizable group proceeds sufficiently, and the alignment of the polymerizable liquid crystal compound is not easily disturbed.

[0082] In the present invention, the polymerizable liquid crystal composition preferably contains a solvent since it is usually applied to a substrate etc. in a state of being dissolved in a solvent. The solvent is preferably a solvent capable of dissolving the polymerizable liquid crystal compounds constituting the polymerizable liquid crystal composition such as the polymerizable liquid crystal compounds (I) and (II), and is preferably a solvent inactive to the polymerization reaction of the polymerizable liquid crystal compounds. Examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone. These solvents can be used alone or in combination of two or more. Among these, organic solvents are preferred, and alcohol solvents, ester solvents, ketone solvents, chlorine-containing solvents, amide solvents and aromatic hydrocarbon solvents are more preferred.

[0083] The content of the solvent in the polymerizable liquid crystal composition is preferably 50 to 98 parts by mass, more preferably 70 to 95 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal composition. Therefore, the solid content in 100 parts by mass of the polymerizable liquid crystal composition is preferably 2 to 50 parts by mass, more preferably 5 to 30 parts by mass. If the solid content is 50 parts by mass or less, the viscosity of the polymerizable liquid crystal composition tends to be low, the thickness of the film tends to be approximately uniform, and unevenness tends to be less likely to occur. The solid content can be appropriately determined in consideration of the thickness of the liquid crystal cured film to be produced.

[0084] By blending a polymerization inhibitor, the polymerization reaction of the polymerizable liquid crystal compound can be controlled. Examples of the polymerization inhibitor include hydroquinones having a substituent such as hydroquinone and alkyl ether; catechols having a substituent such as alkyl ether, such as butylcatechol; radical scavengers such as pyrogallols and 2,2,6,6-tetramethyl-1-piperidinyloxy radical; thiophenols; β-naphthylamines and β-naphthols. In order to polymerize the polymerizable liquid crystal compound without disturbing the alignment, the content of the polymerization inhibitor is usually 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0085] Furthermore, the photopolymerization initiator can be made highly sensitive by using a sensitizer. Examples of the photosensitizer include xanthones such as xanthone and thioxanthone; anthracenes having anthracene and alkyl ether as a substituent; phenothiazine; and rubrene. Examples of the photosensitizer include xanthones such as xanthone and thioxanthone; anthracenes having anthracene and alkyl ether as a substituent; phenothiazine; and rubrene. The content of the photosensitizer is usually 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.

[0086] Furthermore, the polymerizable liquid crystal composition of the present invention may contain a leveling agent. The leveling agent is an additive that has the function of adjusting the fluidity of the polymerizable liquid crystal composition and making the film obtained by applying the composition flatter, and examples of the leveling agent include silicone-based, polyacrylate-based and perfluoroalkyl-based leveling agents. Specifically, DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, FZ2123 (all manufactured by Dow Corning Toray Co., Ltd.), KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF-4446, TSF4452, TSF4460 (all manufactured by Momentive Performance Materials Co., Ltd.) Japan LLC), Fluorinert (registered trademark) FC-72, FC-40, FC-43, FC-3283 (all manufactured by Sumitomo 3M Limited), Megafac (registered trademark) R-08, R-30, R-90, F-410, F-411, F-443, F-445, F-470, F-477, F-479, F-482, F-483 (all manufactured by DIC Corporation), F-top (trade name) EF301, EF303, EF351, EF352 (all manufactured by Mitsubishi Materials Electronics Co., Ltd.), Surflon (registered trademark) S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40, SA-100 (all manufactured by AGC Seimi Chemical Co., Ltd.), trade names E1830, E5844 (manufactured by Daikin Fine Chemical Research Institute Co., Ltd.), BM-1000, BM-1100, BYK-352, BYK-353 and BYK-361N (all trade names: manufactured by BM Chemie Co., Ltd.), etc. Among them, polyacrylate-based leveling agents and perfluoroalkyl-based leveling agents are preferred.

[0087] The content of the leveling agent in the polymerizable liquid crystal composition is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the polymerizable liquid crystal compound is easily aligned, and the obtained liquid crystal cured film tends to be smoother, which is preferable. The polymerizable liquid crystal composition may contain two or more types of leveling agents.

[0088] The polymerizable liquid crystal composition of the present invention can be prepared by adding additives such as a solvent, a photopolymerization initiator, a polymerization inhibitor, a photosensitizer or a leveling agent to the polymerizable liquid crystal compounds (I) and (II), as necessary, and stirring and mixing the mixture at a predetermined temperature.

[0089] <Retardation film> The polymerizable liquid crystal composition of the present invention has a high solubility in a solvent of the polymerizable liquid crystal compound, and therefore has an excellent effect of suppressing the occurrence of alignment defects caused by undissolved polymerizable liquid crystal compounds or precipitation or deposition of the polymerizable liquid crystal compound during storage. Therefore, by using the polymerizable liquid crystal composition of the present invention, it is possible to form a film without reducing the optical properties that the polymerizable liquid crystal compound can originally exhibit, and it is easy to obtain a liquid crystal cured film having excellent optical properties. Therefore, the present invention also relates to a retardation film comprising a liquid crystal cured film that is a cured product of the polymerizable liquid crystal composition of the present invention and is obtained by curing the polymerizable liquid crystal compound in an aligned state. The retardation film composed of the liquid crystal cured film can fully exhibit the optical properties that the polymerizable liquid crystal compound used can originally exhibit, and can be a retardation film having high optical performance.

[0090] The liquid crystal cured film constituting the retardation film of the present invention may be composed of a homopolymer of the polymerizable liquid crystal compound (I) in an oriented state and a homopolymer of the polymerizable liquid crystal compound (II), or may be composed of a copolymer of the mixture of the polymerizable liquid crystal compounds (I) and (II) in an oriented state. Since the polymerization reaction is easy and a uniform liquid crystal cured film is easily obtained, it is preferable that the liquid crystal cured film constituting the retardation film of the present invention is composed of a copolymer of the mixture of the polymerizable liquid crystal compounds (I) and (II) in an oriented state.

[0091] In one embodiment of the present invention, the retardation film of the present invention is a cured product of the polymerizable liquid crystal composition of the present invention, and includes a liquid crystal cured film having optical properties represented by the following formulas (1), (2), and (3). The liquid crystal cured film is usually a cured product obtained by curing the polymerizable liquid crystal compounds (I) and (II) in a state where they are aligned in the horizontal direction relative to the plane of the liquid crystal cured film (hereinafter, also referred to as a "horizontally aligned liquid crystal cured film"). Re(450) / Re(550)≦1.00 (1) 1.00≦Re(650) / Re(550) (2) 100nm≦Re(550)≦180nm (3) (In the formula, Re(λ) represents an in-plane retardation value of the cured liquid crystal film at a wavelength of λ nm, and Re=(nx(λ)-ny(λ))×d (d represents the thickness of the cured liquid crystal film, nx represents the principal refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film in an index ellipsoid formed by the cured liquid crystal film, and ny represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film and perpendicular to the direction of nx in an index ellipsoid formed by the cured liquid crystal film).)

[0092] When the horizontally aligned liquid crystal cured film satisfies the formulas (1) and (2), the horizontally aligned liquid crystal cured film exhibits a so-called reverse wavelength dispersion, in which the in-plane retardation value at a short wavelength is smaller than the in-plane retardation value at a long wavelength. Since the reverse wavelength dispersion is improved and the optical properties of the retardation film are further improved, Re(450) / Re(550) is preferably 0.70 or more, more preferably 0.78 or more, and also preferably 0.92 or less, more preferably 0.90 or less, even more preferably 0.87 or less, particularly preferably 0.86 or less, and even more particularly preferably 0.85 or less. In addition, Re(650) / Re(550) is preferably 1.00 or more, more preferably 1.01 or more, and even more preferably 1.02 or more.

[0093] The in-plane retardation value can be adjusted by the thickness d of the horizontally aligned liquid crystal cured film. Since the in-plane retardation value is determined by the above formula Re(λ)=(nx(λ)-ny(λ))×d, the three-dimensional refractive index and the film thickness d can be adjusted to obtain a desired in-plane retardation value (Re(λ): in-plane retardation value of the horizontally aligned liquid crystal cured film at a wavelength λ(nm)).

[0094] In addition, when the horizontally aligned liquid crystal cured film satisfies formula (3), the retardation film containing the horizontally aligned liquid crystal cured film functions as a λ / 4 plate, and is excellent in the effect of improving the front reflection hue (effect of suppressing coloration) when an elliptical polarizing plate including the retardation film containing the liquid crystal cured film is applied to an optical display, etc. A more preferable range of the in-plane retardation value is 120 nm≦Re(550)≦170 nm, and an even more preferable range is 130 nm≦Re(550)≦150 nm.

[0095] In another embodiment of the present invention, the retardation film of the present invention is a cured product of the polymerizable liquid crystal composition of the present invention, and includes a liquid crystal cured film having optical properties represented by the following formulas (4), (5), and (6). The liquid crystal cured film is usually a cured product obtained by curing the polymerizable liquid crystal compounds (I) and (II) in a state where they are aligned in a direction perpendicular to the plane of the liquid crystal cured film (hereinafter, also referred to as a "vertically aligned liquid crystal cured film"). Rth(450) / Rth(550)≦1.00 (4) 1.00≦Rth(650) / Rth(550) (5) -100nm≦Rth(550)≦-40nm (6) (In the formula, Rth(λ) represents a retardation value in the thickness direction of the cured liquid crystal film at a wavelength of λ nm, and Rth=((nx(λ)+ny(λ)) / 2-nz)×d (d represents the thickness of the cured liquid crystal film, nx represents the principal refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film in the index ellipsoid formed by the cured liquid crystal film, ny represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film and perpendicular to the direction of nx in the index ellipsoid formed by the cured liquid crystal film, and nz represents the refractive index at a wavelength of λ nm in a direction perpendicular to the plane of the cured liquid crystal film in the index ellipsoid formed by the cured liquid crystal film).)

[0096] When the vertically aligned liquid crystal cured film satisfies the formulas (4) and (5), in an elliptical polarizing plate having a retardation film including the vertically aligned liquid crystal cured film, the decrease in ellipticity can be suppressed on the short wavelength side, and the oblique reflection hue can be improved. The value of Rth(450) / Rth(550) in the vertically aligned liquid crystal cured film is preferably 0.70 or more, more preferably 0.78 or more, and also preferably 0.92 or less, more preferably 0.90 or less, even more preferably 0.87 or less, particularly preferably 0.86 or less, and even more particularly preferably 0.85 or less. In addition, Rth(650) / Rth(550) is preferably 1.0 or more, more preferably 1.01 or more, and even more preferably 1.02 or more.

[0097] In addition, when the vertically aligned liquid crystal cured film satisfies formula (6), the oblique reflection hue can be improved when an elliptical polarizing plate having a retardation film containing the vertically aligned liquid crystal cured film is applied to an organic EL display device. The retardation value Rth(550) in the thickness direction of the vertically aligned liquid crystal cured film is more preferably -90 nm or more, further preferably -80 nm or more, and more preferably -50 nm or less.

[0098] The retardation value in the thickness direction can be adjusted by the thickness d of the liquid crystal cured film. The retardation value is determined by the above formula Rth=((nx(λ)+ny(λ)) / 2-nz)×d, so that the desired retardation value (Rth(λ): retardation value in the thickness direction of the liquid crystal cured film at a wavelength λ(nm)) can be obtained by adjusting the three-dimensional refractive index and the film thickness d.

[0099] The retardation film of the present invention is, for example, A step of forming a coating film of the polymerizable liquid crystal composition of the present invention, drying the coating film, and aligning the polymerizable liquid crystal compound in the polymerizable liquid crystal composition; and A process in which the polymerizable liquid crystal compound is polymerized by light irradiation while maintaining the alignment state, forming a liquid crystal cured film. The composition can be produced by a method comprising the steps of:

[0100] The coating film of the polymerizable liquid crystal composition can be formed by applying the polymerizable liquid crystal composition onto a substrate or onto an alignment film described below. Examples of the substrate include glass substrates and film substrates, but resin film substrates are preferred from the viewpoint of processability. Examples of the resin constituting the film substrate include polyolefins such as polyethylene, polypropylene, and norbornene-based polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid esters; polyacrylic acid esters; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; plastics such as polyphenylene sulfide and polyphenylene oxide. Such resins can be formed into a film by known means such as solvent casting and melt extrusion to form a substrate. The substrate surface may have a protective layer formed from an acrylic resin, a methacrylic resin, an epoxy resin, an oxetane resin, a urethane resin, a melamine resin, or the like, and may be subjected to a surface treatment such as a release treatment such as silicone treatment, a corona treatment, or a plasma treatment.

[0101] Commercially available products may be used as the substrate. Examples of commercially available cellulose ester substrates include cellulose ester substrates manufactured by Fuji Photo Film Co., Ltd., such as Fujitac Film; cellulose ester substrates manufactured by Konica Minolta Opto Co., Ltd., such as "KC8UX2M", "KC8UY", and "KC4UY". Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona (Germany), such as "Topas (registered trademark)", cyclic olefin resins manufactured by JSR Corporation, such as "Arton (registered trademark)", cyclic olefin resins manufactured by Zeon Corporation, such as "ZEONOR (registered trademark)" and "ZEONEX (registered trademark)", and cyclic olefin resins manufactured by Mitsui Chemicals, Inc., such as "Apel" (registered trademark). Commercially available cyclic olefin resin substrates may also be used. Commercially available cyclic olefin resin substrates include cyclic olefin resin substrates manufactured by Sekisui Chemical Co., Ltd., such as "S-Cina (registered trademark)" and "SCA40 (registered trademark)"; cyclic olefin resin substrates manufactured by Optes Inc., such as "ZEONORFILM (registered trademark)"; and cyclic olefin resin substrates manufactured by JSR Corporation, such as "ARTONFILM (registered trademark)."

[0102] From the viewpoints of thinning the retardation film, ease of peeling the substrate, handleability of the substrate, and the like, the thickness of the substrate is usually from 5 to 300 μm, and preferably from 10 to 150 μm.

[0103] Examples of a method for applying the polymerizable liquid crystal composition to a substrate or the like include known methods such as application methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator methods, and printing methods such as flexography.

[0104] Next, the solvent is removed by drying or the like to form a dried coating film. Examples of drying methods include natural drying, ventilation drying, heat drying, and reduced pressure drying. In this case, by heating the coating film obtained from the polymerizable liquid crystal composition, the solvent can be dried and removed from the coating film, and the polymerizable liquid crystal compound can be aligned in a desired direction (for example, horizontal or vertical) relative to the coating film plane. The heating temperature of the coating film can be appropriately determined in consideration of the materials of the polymerizable liquid crystal compound used and the substrate on which the coating film is formed, and the like, but in order to phase-transition the polymerizable liquid crystal compound to a liquid crystal phase state, it is usually necessary that the temperature is equal to or higher than the liquid crystal phase transition temperature. In order to make the polymerizable liquid crystal compound have a desired alignment state while removing the solvent contained in the polymerizable liquid crystal composition, for example, the composition can be heated to a temperature equal to or higher than the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition. The liquid crystal phase transition temperature can be measured, for example, using a polarizing microscope equipped with a temperature control stage, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), or the like. The above-mentioned phase transition temperature in the polymerizable liquid crystal composition of the present invention containing at least the polymerizable liquid crystal compound (I) and the polymerizable liquid crystal compound (II) means a temperature measured using a mixture of polymerizable liquid crystal compounds in which all the polymerizable liquid crystal compounds constituting the polymerizable liquid crystal composition are mixed in the same ratio as the composition in the polymerizable liquid crystal composition.

[0105] The polymerizable liquid crystal composition of the present invention contains at least two polymerizable liquid crystal compounds (I) and (II), and can usually undergo liquid crystal phase transition at a temperature lower than the temperature at which each of the polymerizable liquid crystal compounds (I) and (II) transitions to a liquid crystal phase. Therefore, in the production of a retardation film using the polymerizable liquid crystal composition of the present invention, excessive consumption of thermal energy can be suppressed, and production efficiency can be improved. In addition, since the liquid crystal phase transition can be performed by heating at a relatively low temperature, there is also an advantage that the options for the support substrate on which the polymerizable liquid crystal composition is applied are expanded.

[0106] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type and boiling point of the solvent, and the amount thereof, but is usually 15 seconds to 10 minutes, and preferably 0.5 to 5 minutes.

[0107] The removal of the solvent from the coating film may be performed simultaneously with or separately from the heating of the polymerizable liquid crystal compound to a temperature equal to or higher than the liquid crystal phase transition temperature, but is preferably performed simultaneously from the viewpoint of improving productivity. Before heating the polymerizable liquid crystal compound to a temperature equal to or higher than the liquid crystal phase transition temperature, a preliminary drying step may be provided to adequately remove the solvent in the coating film obtained from the polymerizable liquid crystal composition under conditions in which the polymerizable liquid crystal compound contained in the coating film is not polymerized. Examples of the drying method in the preliminary drying step include natural drying, ventilation drying, heat drying, and reduced pressure drying, and the drying temperature (heating temperature) in the drying step can be appropriately determined depending on the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point, and its amount, etc.

[0108] Next, in the obtained dried coating film, the polymerizable liquid crystal compound is polymerized by light irradiation while maintaining the orientation state of the polymerizable liquid crystal compound, thereby forming a liquid crystal cured film that is a polymer of the polymerizable liquid crystal compound existing in a desired orientation state. Since the polymerizable liquid crystal composition of the present invention can be highly polymerized by light irradiation such as high-intensity ultraviolet light while suppressing damage to the polymerizable liquid crystal compound, a photopolymerization method is usually used as a polymerization method. In photopolymerization, the light irradiated to the dried coating film is appropriately selected according to the type of polymerization initiator contained in the dried coating film, the type and amount of the polymerizable liquid crystal compound. Specific examples thereof include one or more types of light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays, and γ-rays, and active electron beams. Among them, ultraviolet light is preferred in terms of ease of controlling the progress of the polymerization reaction and the ability to use photopolymerization devices that are widely used in this field, and it is preferable to select the types of polymerizable liquid crystal compound and polymerization initiator contained in the polymerizable liquid crystal composition so that they can be photopolymerized by ultraviolet light. In addition, during polymerization, the polymerization temperature can be controlled by irradiating light while cooling the dried coating film with an appropriate cooling means. By adopting such a cooling means, polymerization of the polymerizable liquid crystal compound can be carried out at a lower temperature, and even if a substrate having a relatively low heat resistance is used, a liquid crystal cured film can be appropriately formed. In addition, it is also possible to promote the polymerization reaction by increasing the polymerization temperature within a range in which no problems due to heat during light irradiation (such as deformation of the substrate due to heat) occur. During photopolymerization, a patterned cured film can also be obtained by performing masking or development.

[0109] Examples of the light source of the active energy rays include a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave excited mercury lamp, and a metal halide lamp.

[0110] The UV irradiation intensity is usually 10 to 3,000 mW / cm2 The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating a photopolymerization initiator. The time for light irradiation is usually 0.1 seconds to 10 minutes, preferably 0.1 seconds to 5 minutes, more preferably 0.1 seconds to 3 minutes, and further preferably 0.1 seconds to 1 minute. When irradiating once or multiple times with such ultraviolet irradiation intensity, the integrated light amount is 10 to 3,000 mJ / cm. 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 It is.

[0111] The thickness of the liquid crystal cured film can be appropriately selected depending on the optical display to which it is applied, etc. It is preferably 0.2 to 3 μm, more preferably 0.2 to 2 μm.

[0112] The coating film of the polymerizable liquid crystal composition may be formed on an alignment film. The alignment film has an alignment regulating force that aligns the polymerizable liquid crystal compound in a desired direction. For example, there is a horizontal alignment film that has an alignment regulating force that aligns the polymerizable liquid crystal compound in the horizontal direction, and a vertical alignment film that has an alignment regulating force that aligns the polymerizable liquid crystal compound in the vertical direction. The alignment regulating force can be arbitrarily adjusted by the type of alignment film, the surface state, the rubbing conditions, etc., and when the alignment film is formed of a photoalignable polymer, it can be arbitrarily adjusted by the polarized light irradiation conditions, etc.

[0113] The alignment film is preferably one that has solvent resistance such that the polymerizable liquid crystal composition is not dissolved by coating, etc., and also has heat resistance in the heat treatment for removing the solvent and for orienting the polymerizable liquid crystal compound described below. Examples of the alignment film include an alignment film containing an alignment polymer, a photoalignment film, a groove alignment film having a concave-convex pattern or a plurality of grooves on the surface, and a stretched film stretched in the alignment direction, and the like, and a photoalignment film is preferred from the viewpoint of the accuracy of the alignment angle and quality.

[0114] Examples of the oriented polymer include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and polyamic acids, which are hydrolyzates thereof, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among them, polyvinyl alcohol is preferred. The oriented polymers can be used alone or in combination of two or more kinds.

[0115] An alignment film containing an alignment polymer is usually obtained by applying a composition in which an alignment polymer is dissolved in a solvent (hereinafter also referred to as an "alignment polymer composition") to a substrate and removing the solvent, or by applying an alignment polymer composition to a substrate, removing the solvent, and rubbing (rubbing method). Examples of the solvent include the same solvents as those exemplified above as solvents that can be used in the polymerizable liquid crystal composition.

[0116] The concentration of the orienting polymer in the orienting polymer composition may be within a range in which the orienting polymer material can be completely dissolved in the solvent, and is preferably 0.1 to 20% in terms of solid content relative to the solution, and more preferably about 0.1 to 10%.

[0117] As the oriented polymer composition, a commercially available alignment film material may be used as it is. Examples of commercially available alignment film materials include Sunever (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark, manufactured by JSR Corporation).

[0118] The method for applying the alignable polymer composition to the substrate may be the same as the method exemplified for applying the polymerizable liquid crystal composition to the substrate.

[0119] Methods for removing the solvent contained in the orientable polymer composition include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0120] In order to impart an orientation control force to the orientation film, a rubbing treatment can be performed as necessary (rubbing method). A method for imparting an orientation control force by the rubbing method includes a method in which an orientation polymer composition is applied to a substrate and annealed to bring an orientation polymer film formed on the substrate surface into contact with a rotating rubbing roll wrapped with a rubbing cloth. If masking is performed during the rubbing treatment, multiple regions (patterns) with different orientation directions can also be formed on the orientation film.

[0121] A photo-alignment film is usually obtained by applying a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film forming composition") to a substrate, removing the solvent, and then irradiating the substrate with polarized light (preferably polarized UV). Photo-alignment films are also advantageous in that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.

[0122] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it includes groups involved in photoreactions that induce molecular alignment or are the origin of liquid crystal alignment ability, such as isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, caused by irradiation with light. Among them, groups involved in dimerization reaction or photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group, a group having an unsaturated bond, particularly a double bond, is preferred, and a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) is particularly preferred.

[0123] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having an azoxybenzene structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.

[0124] Among them, photoreactive groups involved in photodimerization are preferred, and cinnamoyl and chalcone groups are preferred because the amount of polarized light irradiation required for photoalignment is relatively small and a photoalignment film having excellent thermal stability and stability over time is easily obtained. As the polymer having a photoreactive group, one having a cinnamoyl group such that the terminal of the polymer side chain has a cinnamic acid structure is particularly preferred.

[0125] A photo-alignment layer can be formed on a substrate by applying the photo-alignment film-forming composition on the substrate. The solvent contained in the composition can be the same as the solvents exemplified above as the solvents usable for the polymerizable liquid crystal composition, and can be appropriately selected depending on the solubility of the polymer or monomer having a photoreactive group.

[0126] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted depending on the type of polymer or monomer and the thickness of the intended photo-alignment film, but is preferably at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass, based on the mass of the composition for forming a photo-alignment film. The composition for forming a photo-alignment film may contain a polymer material such as polyvinyl alcohol or polyimide, or a photosensitizer, within a range that does not significantly impair the properties of the photo-alignment film.

[0127] The method of applying the composition for forming a photo-alignment film to a substrate may be the same as the method of applying the oriented polymer composition to a substrate. Examples of the method of removing the solvent from the applied composition for forming a photo-alignment film include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0128] The polarized light may be irradiated by directly irradiating the polarized UV light onto the composition for forming a photo-aligned film coated on the substrate after removing the solvent, or by irradiating the polarized light from the substrate side and transmitting the polarized light. In addition, it is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is particularly preferable. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferable. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are preferable because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. The light from the light source can be irradiated by passing through an appropriate polarizer to irradiate the polarized UV light. As such a polarizer, a polarizing filter, a polarizing prism such as a Glan-Thompson or Glan-Taylor type polarizer, or a wire grid type polarizer can be used.

[0129] If masking is performed during rubbing or polarized light irradiation, a plurality of regions (patterns) in which the liquid crystal alignment directions are different can be formed.

[0130] A groove alignment film is a film that has a concave-convex pattern or multiple grooves on the film surface. When a polymerizable liquid crystal compound is applied to a film with multiple equally spaced linear grooves, the liquid crystal molecules are aligned in the direction along the grooves.

[0131] Methods for obtaining a groove alignment film include a method in which the surface of a photosensitive polyimide film is exposed to light through an exposure mask having slits in a pattern shape, followed by development and rinsing to form an uneven pattern; a method in which a layer of uncured UV-curable resin is formed on a plate-shaped master having grooves on its surface, the formed resin layer is transferred to a substrate and then cured; and a method in which a roll-shaped master having multiple grooves is pressed against an uncured UV-curable resin film formed on a substrate to form unevenness, followed by curing.

[0132] The thickness of the alignment film (alignment film containing an alignment polymer or photoalignment film) is usually in the range of 10 to 10,000 nm, preferably in the range of 10 to 1000 nm, more preferably 10 to 500 nm or less, even more preferably 10 to 300 nm, and particularly preferably 50 to 250 nm.

[0133] <Elliptical polarizing plate> The present invention includes an elliptically polarizing plate comprising the retardation film of the present invention and a polarizing film. The polarizing film is a film having a polarizing function, and examples of the polarizing film include a stretched film having a dye having anisotropy adsorbed thereon, a film coated with a dye having anisotropy, and the like, which includes a polarizer, etc. Examples of the dye having anisotropy include a dichroic dye.

[0134] A film including, as a polarizer, a stretched film having adsorbed thereon a dye having absorption anisotropy is usually produced by uniaxially stretching a polyvinyl alcohol-based resin film, dyeing the polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye, treating the polyvinyl alcohol-based resin film having the adsorbed dichroic dye with an aqueous boric acid solution, and washing the film with water after the treatment with the aqueous boric acid solution, and then sandwiching the film between a transparent protective film via an adhesive on at least one surface of the polarizer produced through these steps.

[0135] Polyvinyl alcohol resins are obtained by saponifying polyvinyl acetate resins. As polyvinyl acetate resins, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith are used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.

[0136] The degree of saponification of the polyvinyl alcohol resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can also be used. The degree of polymerization of the polyvinyl alcohol resin is usually about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.

[0137] Such a polyvinyl alcohol-based resin is used as a raw film for a polarizing film. The method for forming a film of the polyvinyl alcohol-based resin is not particularly limited, and the film can be formed by a known method. The thickness of the polyvinyl alcohol-based raw film can be, for example, about 10 to 150 μm.

[0138] The uniaxial stretching of the polyvinyl alcohol-based resin film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during the boric acid treatment. It is also possible to perform the uniaxial stretching at these multiple stages. In the uniaxial stretching, the film may be uniaxially stretched between rolls having different peripheral speeds, or may be uniaxially stretched using a heated roll. The uniaxial stretching may be dry stretching in which stretching is performed in the atmosphere, or wet stretching in which stretching is performed in a state where the polyvinyl alcohol-based resin film is swollen using a solvent. The stretching ratio is usually about 3 to 8 times.

[0139] Dyeing of a polyvinyl alcohol-based resin film with a dichroic dye is carried out, for example, by a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing the dichroic dye.

[0140] Specifically, iodine or a dichroic organic dye is used as the dichroic pigment. Examples of the dichroic organic dye include a dichroic direct dye made of a disazo compound such as CIDIRECT RED 39, and a dichroic direct dye made of a compound such as trisazo or tetrakisazo. It is preferable that the polyvinyl alcohol resin film is immersed in water before the dyeing process.

[0141] When iodine is used as the dichroic dye, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing iodine and potassium iodide is usually adopted. The content of iodine in this aqueous solution is usually about 0.01 to 1 part by mass per 100 parts by mass of water. The content of potassium iodide is usually about 0.5 to 20 parts by mass per 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40°C. The immersion time in this aqueous solution (dyeing time) is usually about 20 to 1,800 seconds.

[0142] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing a water-soluble dichroic dye is usually adopted. The content of the dichroic organic dye in this aqueous solution is usually 1×10 -4 ~10 parts by mass, preferably 1 × 10 -3 ~1 part by mass, more preferably 1 × 10 -3 ~1×10 -2 The amount of the dye in the aqueous solution is expressed by parts by mass. This aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing assistant. The temperature of the aqueous dichroic dye solution used for dyeing is usually about 20 to 80° C. The immersion time in the aqueous solution (dyeing time) is usually about 10 to 1,800 seconds.

[0143] The boric acid treatment after dyeing with a dichroic dye can usually be carried out by immersing the dyed polyvinyl alcohol resin film in an aqueous boric acid solution. The content of boric acid in this aqueous boric acid solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. When iodine is used as the dichroic dye, this aqueous boric acid solution preferably contains potassium iodide, and in this case, the content of potassium iodide is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the aqueous boric acid solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually 50°C or higher, preferably 50 to 85°C, and more preferably 60 to 80°C.

[0144] The polyvinyl alcohol-based resin film after the boric acid treatment is usually washed with water. The washing can be performed, for example, by immersing the boric acid-treated polyvinyl alcohol-based resin film in water. The temperature of the water used in the washing is usually about 5 to 40° C. The immersion time is usually about 1 to 120 seconds.

[0145] After washing with water, a drying treatment is carried out to obtain a polarizer. The drying treatment can be carried out using, for example, a hot air dryer or a far-infrared heater. The temperature for the drying treatment is usually about 30 to 100°C, and preferably 50 to 80°C. The time for the drying treatment is usually about 60 to 600 seconds, and preferably 120 to 600 seconds. The moisture content of the polarizer is reduced to a practical level by the drying treatment. The moisture content is usually about 5 to 20 mass%, and preferably 8 to 15 mass%. When the moisture content is in the above range, a polarizer having appropriate flexibility and excellent thermal stability is easily obtained.

[0146] The thickness of the polarizer obtained by subjecting the above-mentioned polyvinyl alcohol-based resin film to uniaxial stretching, dyeing with a dichroic dye, treating with boric acid, washing with water and drying is preferably 5 to 40 μm.

[0147] Examples of the film coated with a dye having absorption anisotropy include a film obtained by coating a composition containing a dichroic dye having liquid crystal properties or a composition containing a dichroic dye and a polymerizable liquid crystal compound. The film preferably has a protective film on one or both sides. Examples of the protective film include the same resin film as exemplified above as a substrate that can be used in the production of a liquid crystal cured film.

[0148] The thinner the film coated with the dye having absorption anisotropy, the better. From the viewpoints of strength and processability, the thickness of the film is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.

[0149] Specific examples of the film coated with a dye having absorption anisotropy include the films described in JP-A-2013-33249 and the like.

[0150] A polarizing film is obtained by laminating a transparent protective film on at least one surface of the polarizer thus obtained via an adhesive. As the transparent protective film, a transparent film similar to the resin film exemplified above as a substrate usable for producing the liquid crystal cured film constituting the retardation film can be preferably used.

[0151] The elliptical polarizing plate of the present invention is composed of the retardation film of the present invention and a polarizing film. For example, the retardation film of the present invention and the polarizing film are laminated via an adhesive layer or a pressure-sensitive adhesive layer, etc., to obtain the elliptical polarizing plate of the present invention.

[0152] In one aspect of the present invention, when the retardation film of the present invention containing a liquid crystal cured film and a polarizing film are laminated, it is preferable to laminate them so that the angle between the slow axis (optical axis) of the liquid crystal cured film constituting the retardation film and the absorption axis of the polarizing film is 45±5°.

[0153] The elliptical polarizing plate of the present invention may have a structure similar to that of a conventional general elliptical polarizing plate, or a polarizing film and a retardation film. Examples of such structures include an adhesive layer (sheet) for attaching the elliptical polarizing plate to a display element or the like constituting an optical display, and a protective film used for the purpose of protecting the surface of the polarizing film or retardation film from scratches and dirt.

[0154] The elliptically polarizing plate of the present invention can be used in various display devices. A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of the display device include a liquid crystal display device, an organic electroluminescence (EL) display device, an inorganic electroluminescence (EL) display device, a flexible image display device, a touch panel display device, an electron emission display device (e.g., a field emission display device (FED) and a surface field emission display device (SED)), electronic paper (a display device using electronic ink or an electrophoretic element, a plasma display device, a projection display device (e.g., a grating light valve (GLV) display device, a display device having a digital micromirror device (DMD)), and a piezoelectric ceramic display. The liquid crystal display device includes any of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection liquid crystal display device. These display devices may be display devices that display two-dimensional images, or may be stereoscopic display devices that display three-dimensional images. In particular, the elliptical polarizing plate of the present invention can be suitably used for an organic electroluminescence (EL) display device and an inorganic electroluminescence (EL) display device. These display devices (optical displays) can exhibit good image display characteristics by being provided with the elliptical polarizing plate of the present invention having excellent optical properties.

[0155] A flexible image display device having the elliptically polarizing plate of the present invention preferably further has a window and a touch panel touch sensor. A flexible image display device is, for example, composed of a laminate for a flexible image display device and an organic EL display panel, and the laminate for a flexible image display device is disposed on the viewing side of the organic EL display panel and is configured to be foldable. The laminate for a flexible image display device may include a window, a touch panel touch sensor, etc., in addition to the above-mentioned elliptically polarizing plate of the present invention. The order of lamination of these components is arbitrary, but it is preferable that they are laminated in the order of a window, an elliptically polarizing plate, and a touch panel touch sensor, or in the order of a window, a touch panel touch sensor, and an elliptically polarizing plate, from the viewing side.

[0156] It is preferable that an elliptically polarizing plate is present on the viewing side of the touch panel touch sensor, since the pattern of the touch panel touch sensor is less visible and the visibility of the displayed image is improved. Each member can be laminated using an adhesive, a pressure sensitive adhesive, etc. In addition, the laminate for a flexible image display device can include a light shielding pattern formed on at least one surface of any one of the layers of the window, the elliptically polarizing plate, and the touch panel touch sensor.

[0157] The window is disposed on the viewing side of the flexible image display device and serves to protect other components from external impacts or environmental changes such as temperature and humidity. Conventionally, glass has been used as such a protective layer, but the window in the flexible image display device is not rigid like glass and has flexible properties. The window is made of a flexible transparent substrate and may include a hard coat layer on at least one surface.

[0158] The window, touch panel touch sensor, and the like constituting the laminate for a flexible image display device are not particularly limited, and conventionally known ones can be adopted. EXAMPLES

[0159] The present invention will now be described in more detail with reference to the following examples. In the examples, "%" and "parts" mean "% by mass" and "parts by mass", respectively, unless otherwise specified.

[0160] Example 1: Production of polymerizable liquid crystal compound (A-1) A polymerizable liquid crystal compound represented by the following formula (A-1) (hereinafter referred to as "polymerizable liquid crystal compound (A-1)") was synthesized according to the following scheme.

[0161] [ka]

[0162] A 100mL-four-neck flask equipped with a Dimroth condenser and a thermometer was filled with nitrogen, and 1.00 parts of a compound represented by formula (D-1), 1.05 parts of a compound represented by formula (E-1), 0.02 parts of dimethylaminopyridine (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.), 0.2 parts of dibutylhydroxytoluene (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.), and 30 parts of chloroform (manufactured by Kanto Chemical Co., Ltd.) were added and mixed, and then 1.92 g of IPC (manufactured by Wako Pure Chemical Industries, Ltd.) was further added using a dropping funnel, and these were reacted at 0°C overnight. After the reaction was completed, insoluble components were removed by filtration. The obtained chloroform solution was dropped into methanol (manufactured by Wako Pure Chemical Industries, Ltd.) of 3 times the weight of the chloroform contained in the solution, and a solid was precipitated. The precipitated solid was then filtered off, washed three times with 20 g of methanol, and dried under reduced pressure at 40° C. to obtain 7.49 g of polymerizable liquid crystal compound (A-1). The yield of polymerizable liquid crystal compound (A-1) was 38% based on compound (E-1).

[0163] [Example 2: Production of polymerizable liquid crystal compound (A-2)] A polymerizable liquid crystal compound represented by formula (A-2) (hereinafter referred to as "polymerizable liquid crystal compound (A-2)") was produced in the same manner as in Example 1, except that a compound represented by formula (D-2) shown below was used instead of the compound represented by formula (D-1).

[0164] [ka]

[0165] [ka]

[0166] [Example 3: Production of polymerizable liquid crystal compound (A-3)] A polymerizable liquid crystal compound represented by formula (A-3) (hereinafter referred to as "polymerizable liquid crystal compound (A-3)") was produced in the same manner as in Example 1, except that a compound represented by formula (D-4) was used instead of the compound represented by formula (D-1).

[0167] [ka]

[0168] Comparative Example 1 A polymerizable liquid crystal compound represented by formula (A-4) (hereinafter referred to as "polymerizable liquid crystal compound (A-4)") was synthesized in the same manner as in Example 1, except that no compound represented by formula (E-1) was used, and 1.00 part of a compound represented by formula (F-1) and 1.90 parts of a compound represented by formula (D-1) were used.

[0169] [ka]

[0170] Comparative Example 2 A polymerizable liquid crystal compound represented by formula (A-5) (hereinafter referred to as "polymerizable liquid crystal compound (A-5)") was synthesized in the same manner as in Example 1, except that no compound represented by formula (E-1) was used, and 1.00 part of a compound represented by formula (F-1) and 1.90 parts of a compound represented by formula (D-2) were used.

[0171] [ka]

[0172] Comparative Example 3 A polymerizable liquid crystal compound represented by formula (A-6) (hereinafter referred to as "polymerizable liquid crystal compound (A-6)") was synthesized in the same manner as in Example 1, except that no compound represented by formula (E-1) was used, and 1.00 part of a compound represented by formula (F-1) and 1.90 parts of a compound represented by formula (D-3) were used.

[0173] [ka]

[0174] Comparative Example 4 A polymerizable liquid crystal compound represented by formula (A-7) (hereinafter referred to as "polymerizable liquid crystal compound (A-7)") was synthesized in the same manner as in Example 1, except that no compound represented by formula (E-1) was used, and 1.00 part of a compound represented by formula (F-1) and 1.90 parts of a compound represented by formula (D-4) were used.

[0175] [ka]

[0176] [Measurement of solubility] At 25°C, 1g of each of two organic solvents (o-xylene and cyclopentanone) and a stirrer were placed in a vial tube, and while stirring with a magnetic stirrer (HS-30DN, AS ONE), the polymerizable liquid crystal compound (A-1) of Example 1 was added until the remaining part was visually confirmed. After stirring for 2 hours from the time when the remaining part was confirmed, the resulting mixture was analyzed by HPLC to determine the solubility after confirming that there was remaining part (analyzer: HPLC (Shimadzu Corporation), column used: L-Column ODS 3μm (3mm×150mm), mobile phase A: 0.1% (v / v)-trifluoroacetic acid / water, mobile phase B: 0.1% (v / v)-trifluoroacetic acid / acetonitrile, injection amount: 5μL, detection wavelength: 220nm, oven temperature: 40°C, flow rate: 0.5mL / min). The solubility in each organic solvent was measured in the same manner for the polymerizable liquid crystal compounds of Examples 2 and 3 and Comparative Examples 1 to 4. The obtained results are shown in Table 1.

[0177] [Table 1]

[0178] It was confirmed that the polymerizable liquid crystal compounds according to the present invention (Examples 1 to 3) can have improved solubility compared to the polymerizable liquid crystal compounds of Comparative Examples 1 to 4 having a symmetric structure centered on the alicyclic hydrocarbon group corresponding to M in formula (I).

[0179] [Preparation of composition for forming photoalignment film] The following components were mixed, and the resulting mixture was stirred at 80° C. for 1 hour to obtain a composition for forming a photoalignment film (1). Polymer with photoreactive groups: 1 part [ka] (Number average molecular weight approximately 29000) Solvent: Propylene glycol monomethyl ether: 99 parts

[0180] [Preparation of liquid crystal cured film forming composition (1)] The following components were mixed, and the resulting mixture was stirred at 80° C. for 1 hour to obtain a liquid crystal cured film-forming composition (1). The following polymerizable liquid crystal compound (B-1) was synthesized by the method described in JP-A-2010-31223.

[0181] Polymerizable liquid crystal compound (B-1): 26 parts [ka] Polymerizable liquid crystal compound (A-1) of Example 1: 10 parts Polymerization initiator: 2-Dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure® 369; manufactured by Ciba Specialty Chemicals) 2 parts Leveling agent: 0.1 part of polyacrylate compound (BYK-361N; manufactured by BYK-Chemie) Polymerization inhibitor: Dibutylhydroxytoluene (Wako Pure Chemical Industries, Ltd.) 0.1 part Solvent: N-methyl-2-pyrrolidinone 160 parts, cyclopentanone 240 parts

[0182] [Production of Optical Film] A cycloolefin polymer film (COP) (ZF-14, Zeon Corporation) was treated once with a corona treatment device (AGF-B10, Kasuga Electric Co., Ltd.) under conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface was coated with a photoalignment film-forming composition (1) using a bar coater, dried at 80°C for 1 minute, and then irradiated with 100 mJ / cm using a polarized UV irradiation device (SPOT CURE SP-7, Ushio Inc.). 2 Next, the liquid crystal cured film-forming composition (1) was applied onto the obtained photo-alignment film using a bar coater, dried at 120°C for 1 minute, and then irradiated with ultraviolet light using a high-pressure mercury lamp (UniCure (registered trademark) VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, wavelength: 365 nm, cumulative light amount at wavelength 365 nm: 1000 mJ / cm2). 2 ) to prepare an optical film.

[0183] [Measurement of optical properties] The front retardation value of the optical film was measured by a measuring instrument (KOBRA-WR, manufactured by Oji Scientific Instruments). Since the cycloolefin polymer film used as the substrate does not have birefringence, the value obtained by measuring the above optical film including the COP film with the measuring instrument is substantially the front retardation value of the liquid crystal cured film prepared on the COP film. The obtained optically measured front retardation values ​​were measured at wavelengths of 450 nm, 550 nm, and 650 nm, respectively, and [Re(450) / Re(550)] (referred to as α) and [Re(650) / Re(550)] (referred to as β) were calculated, and the values ​​shown below were obtained. Re(450)=125nm Re(550)=135nm Re(650)=137nm Re(450) / Re(550)=0.91 Re(650) / Re(550)=1.01

[0184] The refractive index of the obtained optical film was confirmed to exhibit reverse wavelength dispersion, since the α value was 1 or less and the β value was 1 or more. This shows that the optical film formed from the polymerizable liquid crystal composition of the present invention is capable of uniform polarization conversion in a wide wavelength range. [Industrial Applicability]

[0185] According to the present invention, a composition having improved solubility in a solvent of a polymerizable liquid crystal compound can be obtained. Furthermore, an optical film capable of uniform polarization conversion in a wide wavelength range can be produced from the composition.

Claims

1. Formula (I): 【Chemistry 1】 [In formula (I), M represents a divalent alicyclic hydrocarbon group, a hydrogen atom contained in the divalent alicyclic hydrocarbon group is optionally substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent alicyclic hydrocarbon group is optionally substituted by an oxygen atom, a sulfur atom, or a nitrogen atom; B 1 and B 2 each independently represents an alkylene group having 1 to 4 carbon atoms, —O—, —S—, —R a1 OR a2 -, -R a3 COOR a4 -, -R a5 O.C.O.R. a6 -, -R a7 O.C. = O.R. a8 -, -OR b O-, -C(=O)-NR c -, -N=N-, -CR c =CR d - or -C≡C-, where R a1 ~R a8 are each independently a single bond or an alkylene group having 1 to 4 carbon atoms; R b is an alkylene group having 1 to 4 carbon atoms, R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom, A 1 and A 2 each independently represents a divalent alicyclic hydrocarbon group or aromatic group, a hydrogen atom contained in the divalent alicyclic hydrocarbon group or aromatic group is optionally substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent alicyclic hydrocarbon group or aromatic group is optionally substituted by an oxygen atom, a sulfur atom, or a nitrogen atom, L 1 and L 2 each independently represents -O-, -COO-, or -OCO-; E a and E b each independently represents an alkanediyl group having 1 to 12 carbon atoms, wherein a hydrogen atom contained in the alkanediyl group may be substituted by an alkyl group having 1 to 4 carbon atoms or a halogen atom, 1 Or L 2 -CH is not adjacent to 2 - may be replaced by -O- or -S- (provided that E a and E b When a plurality of -O- and / or -S- are present in the ring, they are not adjacent to each other. P is an acryloyloxy group or a methacryloyloxy group; E a The total number of carbon atoms in the group represented by b N1 is 2 to 6, N2 is 6 to 12, and the relationship of 1<N2-N1<10 is satisfied, where N1 is the smaller of the total numbers of carbon atoms in the group represented by the formula (I) and N2 is the larger of the total numbers of carbon atoms in the group represented by the formula (I), N1 is 2 to 6, N2 is 6 to 12, and 1<N2-N1<10 is satisfied. A polymerizable liquid crystal compound represented by the formula:

2. 2. The polymerizable liquid crystal compound according to claim 1, wherein M is a divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms.

3. A 1 and A 2 each independently represents a divalent aromatic group, a hydrogen atom contained in the divalent aromatic group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom.

4. B 1 and B 2 The polymerizable liquid crystal compound according to claim 1 , wherein each of the groups independently represents —COO— or —OCO—.

5. A polymerizable liquid crystal compound according to any one of claims 1 to 4 and a compound of formula (II): 【Chemistry 2】 [In formula (II), Ar is a divalent group having at least one aromatic ring, and the aromatic ring constituting the divalent group may contain at least one of a nitrogen atom, an oxygen atom, and a sulfur atom, and the total number N of π electrons contained in the aromatic rings constituting Ar is π is greater than or equal to 12 and less than 36, G 1 and G 2 each independently represents a divalent alicyclic hydrocarbon group, a hydrogen atom contained in the alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and —CH 2 - may be replaced by -O-, -S- or -NH-; B 3 and B 4 each independently represents a single bond or a divalent linking group, A 3 and A 4 each independently represents a divalent alicyclic hydrocarbon group having 3 to 20 carbon atoms or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a hydrogen atom contained in the alicyclic hydrocarbon group and the aromatic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms which may be substituted with a fluorine atom, an alkoxy group having 1 to 4 carbon atoms which may be substituted with a fluorine atom, a cyano group or a nitro group, and —CH 2 - is -O-, -S- or -NR 1 -, -CH(-)- contained in the alicyclic hydrocarbon group may be replaced by -N(-)-, R 1 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, L 3 ~L 6 each independently represents -O-, -COO-, or -OCO-; E c and E d each independently represents an alkanediyl group having 1 to 17 carbon atoms, a hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and —CH 2 - may be replaced by -O- or -CO-; P 1 and P 2 each independently represents a polymerizable group. and a polymerizable liquid crystal compound represented by the formula:

6. The polymerizable liquid crystal composition according to claim 5 , wherein the polymerizable liquid crystal compound represented by formula (II) exhibits a maximum absorption in the wavelength range of 300 nm or more and 400 nm or less.

7. The polymerizable liquid crystal composition according to claim 5 or 6, comprising the polymerizable liquid crystal compound represented by formula (II) in an amount of 0.1 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the polymerizable liquid crystal compound represented by formula (I).

8. A retardation film comprising a liquid crystal cured film obtained by curing the polymerizable liquid crystal composition according to any one of claims 5 to 7, the liquid crystal composition being cured in a state in which the polymerizable liquid crystal compound in the polymerizable liquid crystal composition is aligned.

9. The liquid crystal cured film is represented by the formulas (1), (2) and (3): Re(450) / Re(550)≦1.00 (1) 1.00≦Re(650) / Re(550) (2) 100 nm≦Re(550)≦180 nm (3) [In the formula, Re(λ) represents an in-plane retardation value of the cured liquid crystal film at a wavelength of λ nm, and Re=(nx(λ)-ny(λ))×d (d represents the thickness of the cured liquid crystal film, nx represents the principal refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film in an index ellipsoid formed by the cured liquid crystal film, and ny represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film and perpendicular to the direction of nx in an index ellipsoid formed by the cured liquid crystal film). The retardation film according to claim 8 , having optical properties represented by:

10. The liquid crystal cured film is represented by the formulas (4), (5) and (6): Rth(450) / Rth(550)≦1.00 (4) 1.00≦Rth(650) / Rth(550) (5) -100nm≦Rth(550)≦-40nm (6) [In the formula, Rth(λ) represents a retardation value in the thickness direction of the cured liquid crystal film at a wavelength of λ nm, and Rth=((nx(λ)+ny(λ)) / 2-nz)×d (d represents the thickness of the cured liquid crystal film, nx represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film in the index ellipsoid formed by the cured liquid crystal film, ny represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the cured liquid crystal film and perpendicular to the direction of nx in the index ellipsoid formed by the cured liquid crystal film, and nz represents the refractive index at a wavelength of λ nm in a direction perpendicular to the plane of the cured liquid crystal film in the index ellipsoid formed by the cured liquid crystal film)] The retardation film according to claim 8 , having optical properties represented by:

11. An elliptically polarizing plate comprising the retardation film according to any one of claims 8 to 10 and a polarizing film.

12. An organic electroluminescence display device comprising the elliptically polarizing plate according to claim 11.

13. A flexible image display comprising the elliptically polarizing plate according to claim 11.

14. The flexible image display device of claim 13, further comprising a window and a touch panel touch sensor.

Citation Information

Patent Citations

  • Direactive mesogenic compounds and intermediates

    JP1998513457A

  • Novel polymerizable liquid crystal compounds

    JP1999513360A

  • Liquid crystal composition, polymer network derived therefrom and method of making same

    JP2009532362A

  • Optical film, polarizing plate, display device, and method of producing optical film

    JP2010024438A

  • Polymerizable acetylene compound

    JP2011184417A